Pharmacognostical characterization and formulation of herbal-based low-cost mosquito repellents from Elettaria cardamomum (Linn.) seed by using natural binder - Rajat Das; Prosanta Pal; Sonam Bhutia (SpringerOpen, 2021)
Abstract Background In the present scenario, the markets are flooded with chemical-based mosquito repellent products that are proven to be toxic to the human life especially to the children and quite expensive in term of cost. This present investigation was attempted to evaluate the complete pharmacognostical characteristics of Elettaria cardamomum (Linn.) seed and to formulate eco-friendly and cost-effective herbal mosquito repellents of the seed powder by using a natural binder. Results The results of microscopic study of seed confirmed the presence of perisperm, embryo, endosperm and testa (Figs. 4, 5 and 6). The extractive values, moisture contents and ash values were also analysed and found to be alcoholic extract, 4.88% w/w; water extract, 40% w/w; moisture content, 8.6%; total ash, 5% w/w; acid insoluble ash, 1.5% w/w; and water soluble ash, 3.5% w/w (summarized in Tables 1, 2 and 3). From the mosquito repellency test (Table 6), the combination of cardamom seed cake was done with cardamom powder 3/2 + 1/4 spoons, wood powder 3 spoons and chilli powder 1/4 spoon which showed low residual percentage of 15.05%, no irritation and an average burning time of 65 min. The formulated herbal-based mosquito repellents were found to be more effective without any side effects and found less cost too. Conclusion All the ingredients used in the formulation were herbal based and has no side effect on human health. The cost of the cake was Rs. 11.332/- and it can be considered as good mosquito repellent cakes because of its consistent burning ability with no irritating smoke and low residual percentage and high mosquito repellent ability. By utilizing this concept, the researchers can develop herbal, eco-friendly and cost-effective mosquito repellents in future.